Potensi Putak (Corypha utan Lamk) sebagai sumber pati lokal untuk binder wafer pakan: kajian literatur terhadap sifat kimia dan aplikasinya - Lidya Foni; Isma Sandune Paembonan (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Putak (Corypha utan Lamk) is a locally abundant starch source in Eastern Indonesia with emerging potential as a functional binder for feed wafer production. This study aims to analyze the chemical properties of putak starch and its role as a binder in feed wafer production, and to compare it with other commonly used binding materials. The study was conducted using a descriptive approach based on various scientific publications obtained from the Scopus and Google Scholar databases using the keywords: “adhesive, Corypha utan, feed wafer, gelatinization, physical quality, putak, and binder”. This review summarizes current evidence on the chemical composition and techno-functional properties of putak starch in relation to binder performance requirements. Putak contains high carbohydrate levels (85–87%) and substantial starch content (64–67%), with an amylose–amylopectin ratio comparable to tapioca and sago. These characteristics support desirable functional behaviours, including gelatinisation ability. Comparative literature shows that starch-based binders consistently improve physical qualities, including wafer durability index (WDI), density, impact resistance, total solubility, and water absorption. Given its beneficial properties and local availability, putak represents a promising sustainable alternative to commercial starch binders. Further focused studies are needed to determine binding efficiency and storage stability.